Testing the drivers of the temperature–size covariance using artificial selection. (16th December 2019) - Malerba, Martino E.; Marshall, Dustin J.
Abstract: Body size often declines with increasing temperature. Although there is ample evidence for this effect to be adaptive, it remains unclear whether size shrinking at warmer temperatures is driven by specific properties of being smaller (e.g., surface to volume ratio) or by traits that are correlated with size (e.g., metabolism, growth). We used 290 generations (22 months) of artificial selection on a unicellular phytoplankton species to evolve a 13‐fold difference in volume between small‐selected and large‐selected cells and tested their performance at 22°C (usual temperature), 18°C (−4), and 26°C (+4). Warmer temperatures increased fitness in small‐selected individuals and reduced fitness in large‐selected ones, indicating changes in size alone are sufficient to mediate temperature‐dependent performance. Our results are incompatible with the often‐cited geometric argument of warmer temperature intensifying resource limitation. Instead, we find evidence that is consistent with larger cells being more vulnerable to reactive oxygen species. By engineering cells of different sizes, our results suggest that smaller‐celled species are pre‐adapted for higher temperatures. We discuss the potential repercussions for global carbon cycles and the biological pump under climate warming.